Legal Protection Against Internet Banking Users (Mobile Banking) From Cyber Crime Efforts - Yeremia Juan Dewata (Faculty of Law, Universitas Jenderal Soedirman, 2023)
There have been many violations of the law regarding personal data via the internet and also regarding the financial risks suffered by bank customers. There are rules that protect bank customers using internet banking from cyber crime threats and what legal measures are taken by bank customers using internet banking if the customer's personal data is not protected or experiences personal data leakage. The research design or structure used by the author in this study is the Library Research. There are several laws and regulations governing the personal data of customers as well as banks and bank customers who feel aggrieved by the spread of customer personal information data. Whereas legal protection efforts have been carried out but have not reflected the principle of balance which is really needed. Bank customers who feel disadvantaged due to the distribution of customer personal information data that is used by third parties. The need for better legal protection for customers.Key Words : Consumer, Legal, Banking